LUNTURNYA MORALITAS DALAM DUNIA PENDIDIKAN DI ERA GLOBALISASI DAN KECERDASAN BUATAN (AI) - Zainudin Hasan; Karen Avrilly LB; Ayu Rexy; Devin Alan Victorius (KAMPUS AKADEMIK PUBLISING, 2026)
The development of globalization and artificial intelligence (AI) has brought about significant changes in the world of education. Technology has made it easier to access information, accelerated the learning process, and expanded learning opportunities beyond the boundaries of time and space. However, this progress has also given rise to serious problems in the form of a decline in morality among students and educators. This phenomenon is reflected in a decline in academic honesty, an increase in digital plagiarism, a weakened sense of responsibility, and a diminished respect for teachers and others. The influx of foreign cultural values, coupled with the uncontrolled use of technology, makes education vulnerable to shifts in moral values and character. The decline in morality is not only caused by technological advances, but also by weak character education, a lack of role models, and minimal oversight of the ethical use of AI in learning activities. In many cases, students prioritize the end result over the learning process, while educators often struggle to instill moral values amidst the demands of an achievement-oriented education system. This situation indicates that modern education has not fully achieved a balance between intellectual and moral intelligence. Therefore, a renewed educational paradigm is needed that re-emphasizes the importance of ethics, responsibility, and integrity amidst technological advancements. Integrating character education into all aspects of learning, ethical digital literacy, and exemplary behavior from teachers and parents are key to maintaining the morality of the younger generation. Therefore, the use of AI and globalization should not be a threat to human values, but rather a means to shape students who are not only intellectually intelligent but also morally upright, possessing integrity, and possessing a strong moral conscience.